Discovery of a broadly-neutralizing human antibody that can rescue mice challenged with neurotoxin-rich snake venoms - Ledsgaard, Line (2022)
Snakebite envenoming continues to claim many lives across the globe, necessitating the development of improved therapies. To this end, human monoclonal antibodies may possess advantages over current plasma-derived antivenoms by offering superior safety and improved neutralization capacity. However, as new antivenom products may need to be polyvalent, i.e., target multiple different snake species, without dramatically increasing dose or cost of manufacture, such monoclonal antibodies need to be broadly-neutralizing. Here, we report the establishment of a pipeline for the discovery of high affinity broadly-neutralizing human monoclonal antibodies. We further demonstrate its utility by discovering an antibody that can prevent lethality induced by N. kaouthia whole venom at an unprecedented low molar ratio of one antibody per toxin, and which also prolongs survival of mice injected with Dendroaspis polylepis or Ophiophagus hannah whole venoms.